Repair of the penile suspensory ligament for congenital and acquired pathology. (3rd April 2019) - Ralph, Oliver; Shroff, Nikita; Anfosso, Mattia; Blecher, Gideon; Ralph, David
Abstract : Objective: To review the mechanisms and patient outcomes for men presenting with abnormalities of the penile suspensory ligament (PSL) and their correction. Patients and Methods: We conducted a retrospective review of a total of 118 patients who presented with a variety of PSL abnormalities that necessitated surgical repair from 1993 to 2018. The patients mean (range) age at presentation was 29 (12–60) years with a mean (range) follow up of 8 months (3 months–12 years). The diagnosis was made clinically, often with a history of penile instability, pain or curvature/torsion, which was confirmed on artificial erection testing. Nocturnal tumescent testing and magnetic resonance imaging were used where necessary. The surgical repair was performed by placing non‐absorbable sutures between the tunica albuginea of the penis and the symphysis pubis. Postoperative outcomes were reported in the clinic by direct questioning and a repeat of the investigations above when patients were unsatisfied with the result. Results: The aetiologies and surgical indications in the 118 patients included: abnormality subsequent to sexual trauma ( n = 66); congenital curvature of penis and/or congenital absence/laxity of the ligament ( n = 37); Peyronie's disease ( n = 8); and venogenic erectile dysfunction (ED; n = 7). A good surgical result, as defined by stabilization and straightening of the penis and a return to normal sexual function, was achieved in 85% of the patients and 82% were very satisfied with the outcome. Complications included long‐term ED in four patients. Conclusion: Abnormalities of the PSL are uncommon and often subtle, but with the appropriate diagnosis, a good cosmetic and functional result is usually achievable.